Calculus: Early Transcendentals (2nd Edition)

Published by Pearson
ISBN 10: 0321947347
ISBN 13: 978-0-32194-734-5

Chapter 3 - Derivatives - 3.4 The Product and Quotient Rules - 3.4 Exercises - Page 161: 66



Work Step by Step

$f(x)=\dfrac{4-x^{2}}{x-2}$ Factor the numerator, which is a difference of squares: $f(x)=\dfrac{4-x^{2}}{x-2}=\dfrac{(2-x)(2+x)}{x-2}=...$ Change the sign of the numerator and the sign of the fraction and simplify: $...=-\dfrac{(x-2)(x+2)}{x-2}=-(x+2)=-x-2$ Evaluate the derivative term by term: $f'(x)=-(x)'-(2)'=-1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.